Formulation, optimization, and characterization of amlodipine besylate loaded polymeric nanoparticles. Issue 9 (November 2021) - Chourasiya, Vibha; Bohrey, Sarvesh; Pandey, Archna
The objectives of this work were to formulate and optimize amlodipine besylate loaded polymeric nanoparticles by using factorial design. The emulsion solvent evaporation method was employed successfully to produce the drug loaded polymeric nanoparticles and the optimization was done by the help of the 2 4 factorial design. The effect of the main preparation variables on the dependent variables such as nanoparticle size and % drug entrapment efficiency was studied for the optimization of the nanoparticles. The characterization of these nanoparticles was done by the different parameters such as interaction between the excipients, size, morphology, zeta potential, % drug entrapment efficiency, % process yield, and in-vitro drug release behavior. FTIR, DLS, TEM, AFM, zeta potential studies, and dialysis bag method were performed for this purpose. The in vitro drug release data were analyzed by different kinetic models to know the release mechanism. The optimized nanoparticles were spherical in shape and showed particle size 91.5 ± 4.3 nm, PDI 0.368 ± 0.014, zeta potential −17.5 mV, % drug entrapment efficiency 74.06 ± 2.1%, and % process yield 78.51 ± 1.8%. The release kinetics studies revealed that drug release from the nanoparticles follow the Korsmeyer–Peppas model.